Undergraduates Marketability of Universiti Tun Hussein Onn Malaysia: A Case Study - Ming Foong, Lee (Online Journal for TVET Practitioners, 2022)
The purpose of this research is to determine the employment status of undergraduate students at Universiti Tun Hussein Onn Malaysia (UTHM) from 2015 to 2020. In this study, employment status is defined by (1) job classification and (2) starting salary. This is a case study that focuses on the raw data analysis from the Graduate Tracer Study (Sistem Kajian Pengesan Graduan, SKPC). The Ministry of Higher Education conducts an annual survey to determine employment status after graduation using an online questionnaire. Only those with a Bachelor's degree from UTHM were selected as respondents in this study. The SKPG database data was analysed using descriptive statistics such as frequency and percentage. The findings show that, about 66.6% of graduates, are employed in jobs related to their field of study. Furthermore, in approximately 57% of graduates are employed with starting salaries that are match with their qualifications. It is recommended that the programme be revised to address the issue of starting salary, as well as underemployment.